Gradient discretization of two-phase flows coupled with mechanical deformation in fractured porous media. (15th September 2021) - Bonaldi, Francesco; Brenner, Konstantin; Droniou, Jérôme; Masson, Roland
Abstract: We consider a two-phase Darcy flow in a fractured porous medium consisting in a matrix flow coupled with a tangential flow in the fractures, described as a network of planar surfaces. This flow model is also coupled with the mechanical deformation of the matrix assuming that the fractures are open and filled by the fluids, as well as small deformations and a linear elastic constitutive law. The model is discretized using the gradient discretization method [30], which covers a large class of conforming and non conforming schemes. This framework allows for a generic convergence analysis of the coupled model using a combination of discrete functional tools. Here, we describe the model together with its numerical discretization and, using discrete compactness techniques, we prove a convergence result (up to a subsequence) assuming the non-degeneracy of the phase mobilities and that the discrete solutions remain physical in the sense that, roughly speaking, the porosity does not vanish and the fractures remain open. This is, to our knowledge, the first convergence result for this type of model taking into account two-phase flows in fractured porous media and the non-linear poromechanical coupling. Previous related works consider a linear approximation obtained for a single phase flow by freezing the fracture conductivity [41, 42] . Numerical tests employing the Two-Point Flux Approximation (TPFA) finite volume scheme for the flows and P 2 finite elements for the mechanical deformation are also provided to illustrate the behavior of the solution to the model.